Pengaruh Aglomerasi industri, Angkatan Kerja, Dan Human Capital Investment Terhadap Pertumbuhan Ekonomi Kota Medan Dalam Perspektif Ekonomi Islam - Arieffan Syah; Zuhrinal M. Nawawi; Aqwa Naser Daulay (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of agglomeration, labor force and Human Capital Investment on economic growth in Medan City. This research applies a quantitative approach. industrial concentration that embodies consumption patterns that affect the development of the economy of the surrounding area, then the labor force is able to support the economy to increase its production factors, the last human capital investment / HCI is a field that has sufficient human resources in terms of ability, knowledge, and health that can support economic growth. This research data is obtained from secondary data with the use of data collection methods, namely literature studies and documentation. The use of analysis techniques is multiple linear regression tests utilizing the SPSS23 analysis tool. The results of this study indicate that simultaneously agglomeration (X1), labor (X2), and Human Capital Investment (X3) have a positive and significant effect on economic growth (Y). The results obtained show that simultaneously agglomeration, labor force, and human capital investment have an influence on economic growth in Medan City. Keywords: Agglomeration, Labor Force, Human Capital Investment